Teachers’ Subjective Wellbeing During the Covid-19 Pandemic: Its Relation to Religiosity and Trust in Science - Balbuena, Sherwin E.; Balbuena, Princess Z. (Future Science / FSH-PH Publications, 2023)
This study investigated the association between religiosity and teachers’ subjective wellbeing and between their trust in science and subjective wellbeing during the COVID-19 pandemic. Using a correlational research design, a survey was conducted involving 170 schoolteachers in Southern Bicol, Philippines. Results of the study showed that religiosity and wellbeing had a significant positive linear correlation. Religiosity was found to be a significant predictor of wellbeing. Furthermore, distrust in science and wellbeing had a significant monotonic relationship. Distrust in science was also a significant predictor of subjective wellbeing. This study concludes that when teachers have higher levels of distrust in science, their level of subjective wellbeing deteriorates. On the other hand, when teachers’ level of religiosity becomes high, their subjective wellbeing improves. These two traits of trust may have helped the teachers cope with the emotional stress experienced during the pandemic.